Disease-driven yield losses in wheat (Triticum aestivum) crop under different agroclimatic locations of Punjab - ANAND, SHUBHAM; SANDHU, SARABJOT KAUR (The Indian Journal of Agricultural Sciences, 2024)
The experiments were conducted during winter (rabi) seasons of 2021–22 and 2022–23 at Punjab Agricultural University, Ludhiana, Punjab to examine the yield losses due to diseases in wheat (Triticum aestivum L.) crop under different agroclimatic locations of Punjab. The experiment was conducted in split-plot design (SPD) having three dates of sowing (14th–15th October, 8th–9th November and 3rd–4th December) in main plots and wheat varieties, viz. PBW 725, HD 2967 and HD 3086 with two microclimate modification levels M1 (recommended irrigation) and M2 (additional water sprays) in sub plots, replicated four times. The yellow rust severity was maximum at Ludhiana (56.14%, 57.17%) and Gurdaspur (56.75%, 58.42%) in HD 2967 under early sown conditions in M2 treatment during 2021–22 and 2022–33, respectively. The Karnal bunt incidence was comparatively higher at Ludhiana (18.5% and 13.4%) and Gurdaspur (21.4% and 16.7%) in variety PBW 725 under normal sowing condition in M2 than other treatments during both the years of study, respectively. Grain yield during 2021–22 and 2022–23 was more in early sowing at Ludhiana (43.3 q/ha, 48.1 q/ha) and Gurdaspur (44.5 q/ha, 50.8 q/ha) than other dates of sowing. In variety × microclimate modification levels treatments, grain yield was maximum at Ludhiana (43.1 q/ha, 47.2 q/ha) and Gurdaspur (44.0 q/ha, 50.2 q/ha) in variety PBW 725 under M1 than other treatments during both the years of study. Early date of sowing recorded more yield losses followed by late and normal sowing and losses were more at Gurdaspur as compared to Ludhiana. Average yield losses during 2022–23 were higher i.e. 5.6% and 7.1% as compared to 1.6% and 2.3% during 2021–22 at Ludhiana and Gurdaspur, respectively.